THE IMPACT OF CAR, LDR, BOPO, SIZE, AND NIM ON BANKS FINANCIAL PERFORMANCE - Sugiarto, Aris; Sriyatun, Sriyatun (Ultima Management : Jurnal Ilmu Manajemen, 2024)
Abstract- Banking Return on Assets (ROA) measures operational efficiency and profitability by measuring how well a bank uses its assets to generate cash. ROA is also influenced by macroeconomic conditions, related regulations, and the competitiveness of the banking sector. In an increasingly competitive market, banks must understand these phenomena to improve their profitability and competitiveness. This study seeks to examine the impact of the variables Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Operating Costs and Operating Income (BOPO), bank size (SIZE), and Net Interest Margin (NIM) on Return on Assets (ROA). The study population comprises all conventional banks registered on the Indonesia Stock Exchange (IDX) from 2019 to 2023, totaling 47 banks. The employed sampling approach is total sampling, indicating that the entire population is surveyed, resulting in a sample size of 47 banks across a five-year period. The total data analysed in this study is 235. The employed analytical method is multiple linear regression, supplemented by traditional assumption checks encompassing normality, heteroscedasticity, multicollinearity, and autocorrelation assessments. Hypothesis testing uses t-statistics to evaluate partial regression coefficients and F-statistics to assess simultaneous effects, with a significance threshold of 5% (0.05). The study's results demonstrate that CAR, LDR, BOPO, SIZE, and NIM significantly influence ROA both partially, as the significance value (sig) is below 0.05, and simultaneously on ROA. Keywords: CAR; LDR; BOPO; SIZE; NIM